Model Pembelajaran Numbered Heads Together Efektif Meningkatkan Hasil Belajar Muatan PPKn di Kelas VI Sekolah Dasar - Widodo Widodo; Tarto Tarto (UM Purwokerto Press, 2022)
This study aims to 1) Improve learning outcomes for Civics content through the application of the NHT learning model to class VI students of SD Kerdonmiri II Gunungkidul Regency in 2019/2020) Increase student activity in Civics learning through the application of the NHT learning model to class VI students of SD Kedoniri II II Gunungkidul Regency in 2019/2020. This research is a classroom action research (CAR) conducted at SD Negeri Kerdonmiri II with the research subjects being class VI students, totaling 17 students. Data was collected by means of observation, document analysis, and tests. Analysis of the data used is the percentage of test results. The research process was carried out in two cycles which included four stages, namely the planning stage, the implementation stage, the observation and interpretation stage, and the analysis and reflection stage. process and results. Improving the quality of the learning process is marked by increased student activity in learning activities. The increase in the success of learning to explain Indonesia's free and active foreign policy is marked by an increase in student achievement who can achieve the KKM score, in the pre-cycle students who reach the KKM score of 43%, in the first stage of the cycle it increases to 71%, and in the second cycle it becomes 88%.